(untitled) (Confluenţe Bibliologice, 2017)
The article deals with Svetlana Toma’s biography and activity as Moldovan cinematographic actress. Svetlana Toma was awarded the title of the People’s Artist of Moldova. Svetlana Toma is the best Moldovan actress of the XX Century.